Outras histórias: memórias silenciadas e histórias ignoradas em Itapagipe-MG (1970 2023) - Barbosa, Maria Rita de Jesus (2024)
The proposal of this thesis is to know the Other Histories, which narrate the formation of the society, policy, economy, culture and religion of Itapagipe-MG, from another perspective, from those who did not or does not occupy positions that guarantee privilege or power. To know these Other HIstories, it was needed to search for other authors, narrators, to reach other histories and memories. To know the motivations which hushed up the Other Histories, in the oficial narrative of Itapagipe-MG, who were or who are those hushed up people in Our Histories, why their histories were not written, recognized the necessity of literary work or authors who talk with more intimacy with the object of the research and the people involved. The decolonial authors compose the biggest part of the theorical framework of the research, the choice is related to the theme and the people studied, poor men and women, in your majority black people, who were excluded from the Oficial History of Itapagipe. Those people, with more than 60 years old, residents of neighborhood Pito Acesso and the Rural Community of Douradinho, shared not just individual histories, but also of their groups, communities, where they live and their ancestors lived. As well as memories of their fight for survival, sentimental memories and festivities. The recorded interviews has transformed into one of the main source of knowledge of Other Histories which are part of local History of Itapagipe-MG. The written documentation, acquired in the main public institutions of Itapagipe-MG, Files of the Municipal Executive, of the Municipal Chamber and the Parish are the written sources of this research. In this documents, is represented the view of those who had and have the power in the Municipality over the hushed up people and their living places, urban space as well as the rural. The research does not intend to write a new history for Itapagipe, from the denial of all that has been built until this moment, but include other people, other histories and other memories